Observed appetite and nutrient intake three months after ICU discharge. Issue 3 (June 2019) - Chapple, Lee-anne S.; Weinel, Luke M.; Abdelhamid, Yasmine Ali; Summers, Matthew J.; Nguyen, Thu; Kar, Palash; Lange, Kylie; Chapman, Marianne J.; Deane, Adam M.
Summary: Background & aims: Oral intake is diminished immediately after ICU discharge, yet factors affecting nutritional intake after hospital discharge have not been evaluated. The aim of this study was to evaluate dietary intake and factors which may influence intake - appetite and gastric emptying - 3-months after ICU discharge. Methods: Inception cohort study with ICU survivors compared to healthy subjects. Following an overnight fast, all participants consumed a standardized carbohydrate drink, containing 13 C-octanoic acid, to measure gastric emptying. Dietary intake was assessed by recall of the preceding day and a standard weighed buffet meal 4-h post-drink. Appetite was assessed pre-drink (fasting) and pre- and post-buffet using visual analogue scales. Results: Fifty-one ICU survivors (82% male; 70 ± 9 y; BMI 28 ± 6 kg/m 2 ) and 25 healthy subjects (60% male; 67 ± 12 y; BMI 27 ± 4 kg/m 2 ) were evaluated. From the 24-h recall ICU survivors consumed less calories (ICU 1876 (708) vs. healthy subjects 2291 (834) kcal; p = 0.025) with no difference in macronutrient intake, however reported a lower preference for fat (p < 0.001). Calorie and macronutrient intake from the weighed buffet was similar between groups: calories (ICU: 658 (301) vs. healthy subjects: 736 (325) kcal; p = 0.149); protein (ICU: 37 (19) vs. healthy subjects: 40 (17) g; p = 0.275); fat (ICU: 23 (12) vs healthy subjects: 26 (13) g; p = 0.261); and carbohydrates (ICU: 69 (35) vs. healthy subjects: 79 (42) g; p = 0.141). ICU survivors reported feeling less full regardless of time-point (p = 0.041). There was no difference in the rate of gastric emptying between the two groups (p = 0.216). Conclusions: ICU survivors reported less preference for fat and less calorie consumption than healthy subjects. However, intake of calories and macronutrients at a weighed meal was similar in the two groups, as was the rate of gastric emptying. ICU survivors reported being less full after the test meal, suggesting factors other than appetite may influence intake.